2011
DOI: 10.1021/jo2018125
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Intramolecular Hydroalkoxylation of α-(1-Hydroxy-1-alkyl- and -aryl)methylallenoates by a 5-Endo Mode for Preparation of 2-Alkyl- and 2-Aryl-2,5-dihydrofurans

Abstract: Ethyl α-(1-hydroxy-1-alkyl)methylallenoates and α-(1-hydroxy-1-aryl)methylallenoates containing not only electron-donating groups but also an electron-withdrawing group on the aryl group at the α-position have been shown to undergo an efficient and selective copper-catalyzed intramolecular hydroalkoxylation to give functionalized 3-ethoxycarbonyl-2-alkyl- and -aryl-2,5-dihydrofurans in good to excellent yields through a 5-endo mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 53 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…Intramolecular hydroalkoxylation of α-hydroxymethylallenes is one way to prepare 2,5-dihydrofurans. In 2012, Lee et al, developed a method lying on the use of copper(I) and copper(II) halides as catalysts in the cyclisation of ethyl α-(1-hydroxy-1-alkyl)methylallenoates and α-(1-hydroxy-1-aryl)methylallenoates [ 91 ]. The best conditions are found with CuCl 2 (5 mol %) in DMF at 110 °C ( Scheme 34 ).…”
Section: Coppermentioning
confidence: 99%
“…Intramolecular hydroalkoxylation of α-hydroxymethylallenes is one way to prepare 2,5-dihydrofurans. In 2012, Lee et al, developed a method lying on the use of copper(I) and copper(II) halides as catalysts in the cyclisation of ethyl α-(1-hydroxy-1-alkyl)methylallenoates and α-(1-hydroxy-1-aryl)methylallenoates [ 91 ]. The best conditions are found with CuCl 2 (5 mol %) in DMF at 110 °C ( Scheme 34 ).…”
Section: Coppermentioning
confidence: 99%
“…Among various allenols, extensively investigated reactions was on the α‐allenols to be converted into 2,5‐dihydrofurans under silver catalysis (AgBF 4 or AgNO 3 ) . The regioselectivity favored for 5‐ endo products was also observed in other catalysis using AuCl 3 , LAu(I)X, CuCl 2 , PtCl 2 , and Hg(ClO 4 ) 2 metals, and cyclization of chiral α‐allenols resulted the successful axial‐to‐center chirality transfer 2g–i,4c . A more competitive study was performed with allenyl diols, resulting the cyclization of the more hindered hydroxy group through the allene–metal complexation at the less congested face 2h–k .…”
Section: Introductionmentioning
confidence: 54%
“…Since pyrrole-2-carbaldehydes and products of their reduction, 2-hydroxymethylpyrroles, are known to be among most readily available α-functionalized pyrroles, [46] and the reaction of alcohols with allenes has been studied in some detail, [47][48][49] it is reasonable to propose the following scheme for the construc- However, our experiments have shown that the reduction of N-allenylpyrrole-carbaldehyde under the standard conditions yields a difficult-to-separate mixture of hardly identifiable products. For this reason, the initial strategy has been changed: first, we intended to carry out propargylation of the previously obtained 2-hydroxymethylpyrrole followed by cyclization of the formed adduct.…”
Section: Introductionmentioning
confidence: 96%
“…Since pyrrole‐2‐carbaldehydes and products of their reduction, 2‐hydroxymethylpyrroles, are known to be among most readily available α‐functionalized pyrroles, and the reaction of alcohols with allenes has been studied in some detail, it is reasonable to propose the following scheme for the construction of the pyrrolo‐oxazine ensembles: pyrrole‐ N ‐allenylpyrrole‐ N ‐allenylpyrrole‐carbaldehyde‐ N ‐allenyl‐2‐hydroxymethylpyrrole‐pyrrolo[2,1‐c][1,4]oxazine (Scheme ).…”
Section: Introductionmentioning
confidence: 99%